Identifying Culs-De-Sac courtyard neighbourhoods in Shah Alam / Anniz Fazli Ibrahim Bajunid, Mohamed Yusoff Abbas and Abdul Hadi Nawawi. - Bajunid, Anniz Fazli Ibrahim; Abbas, Mohamed Yusoff; Nawawi, Abdul Hadi (Universiti Teknologi MARA Cawangan Selangor, 2018)
Culs-de-sac in Shah Alam, have begun to take centre stage, especially in the high-end neighbourhood developments. Typically, these neighbourhoods can be easily identified. However, in contrast to developed nations, the local municipality has yet to begin identifying neighbourhood typologies. This paper endeavors to elucidate a sampling or identification process procedures of the cul-de-sac neighbourhood. The cul-de-sac was identified by observing intersection connectivity, link-node ratios, as well as street segment analysis; an assimilation of techniques used in recent western methodologies. Scaled macro to micro map analysis aligned sequentially in sieves, allow for identification of specific cul-de-sac syntax; one in particular is the cul-de-sac courtyards.